Analysis of Factors that Influence APBD Revenues in Regencies/Cities across the Nias Islands - Adilman Baradarkhasan Zega (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine how much influence per capita GRDP, education level, and health level have on district/city APBD revenues throughout the Nias archipelago in 2012 - 2022. The type of research used is descriptive quantitative. The data used is secondary data. This research is a panel data study with the panel data regression analysis method carried out with Eviews 12.0. The results showed that per capita GRDP, education level, and health level variables had a positive effect on district/city APBD revenues for the Nias archipelago in 2012 – 2022.